2011
DOI: 10.1038/gene.2011.31
|View full text |Cite
|
Sign up to set email alerts
|

FoxP3 interacts with linker histone H1.5 to modulate gene expression and program Treg cell activity

Abstract: The forkhead box transcription factor FoxP3 controls the development and function of CD4+CD25+ regulatory T (Treg) cell. FoxP3 modulates gene expression in Treg cells by multiple epigenetic mechanisms that are not clearly defined. We identified FoxP3 interacting proteins in human T cells by co-IP/MS. We discovered that FoxP3 interacted with linker histone H1.5 via the leucine zipper (LZ) domain. Two independent IPEX patient-derived single residue mutations in the LZ of FoxP3 both abrogated its interaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Its Ume6-dependent recruitment to early meiotic genes supports a growing body of evidence that linker histones, although ubiquitous throughout the genome, may play specific roles in the repression of related genes via transcription factor recruitment (10,33,37,48,52). In addition, Hho1 plays a role in genome compaction specifically in the late stages of sporulation.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Its Ume6-dependent recruitment to early meiotic genes supports a growing body of evidence that linker histones, although ubiquitous throughout the genome, may play specific roles in the repression of related genes via transcription factor recruitment (10,33,37,48,52). In addition, Hho1 plays a role in genome compaction specifically in the late stages of sporulation.…”
Section: Discussionmentioning
confidence: 71%
“…The linker histone represses transcription in vitro, but its transcriptional role in vivo has been the subject of debate (7,24). Although H1 has historically been associated with chromatin compaction and general repression, several recent studies have implicated the linker histone in the repression of specific genes via recruitment by transcription factors (10,33,37,45,48,52).…”
mentioning
confidence: 99%
“…This may be achieved through interaction with tissue-specific transcription factors to regulate specific genes during infection. A similar mechanism may exist in human CD4 ϩ CD25 ϩ regulatory T (Treg) cells, where the forkhead transcription factor FoxP3 interacts with linker histone H1.5 to modulate interleukin-2 (IL-2) gene expression in the Treg cells (32). To summarize, it appears that H1 histones, including their variants and associated posttranslational modifications, in conjunction with their reader molecules, have a more specialized function than initially presumed.…”
Section: Discussionmentioning
confidence: 95%
“…1,2 The molecular mechanisms of FOXP3-mediated regulation of gene transcription are not clearly defined, but repression involves interactions with the histone acetyl-transferase TIP60, the histone deacetylase HDAC7, and linker histone H1.5. 3,4 After its discovery in Tregs, it was soon demonstrated that FOXP3 is also expressed transiently in human Tconv cells after TCR activation. [5][6][7][8][9][10][11] Similarly, another Treg-associated transcription factor, Helios, can also be expressed on activation.…”
Section: Introductionmentioning
confidence: 99%